Associations of dietary energy density with body composition and cardiometabolic risk in children with overweight and obesity: role of energy density calculations, under-reporting energy intake and physical activity. Issue 9 (3rd April 2019) - Gomez-Bruton, Alejandro; Arenaza, Lide; Medrano, Maria; Mora-Gonzalez, Jose; Cadenas-Sanchez, Cristina; Migueles, Jairo H.; Muñoz-Hernández, Victoria; Merchan-Ramirez, Elisa; Martinez-Avila, Wendy Daniela; Maldonado, Jose; Oses, Maddi; Tobalina, Ignacio; et al.
Abstract: This study examined (1) the association of dietary energy density from solid (EDS ) and solid plus liquids (EDSL ) with adiposity and cardiometabolic risk factors (CRF) in children with overweight and obesity, (2) the effect of under-reporting on the mentioned associations and (3) whether the association between ED and body composition and CRF is influenced by levels of physical activity. In a cross-sectional design, 208 overweight and obese children (8–12-year-old; 111 boys) completed two non-consecutive 24 h recalls. ED was calculated using two different approaches: EDS and EDSL . Under-reporters were determined with the Goldberg method. Body composition, anthropometry and fasting blood sample measurements were performed. Moderate to vigorous physical activity (MVPA) was registered with accelerometers (7-d-register). Linear regressions were performed to evaluate the association of ED with the previously mentioned variables. Neither EDS nor EDSL were associated with body composition or CRF. However, when under-reporters were excluded, EDS was positively associated with BMI ( P =0·019), body fat percentage ( P =0·005), abdominal fat ( P =0·008) and fat mass index ( P =0·018), while EDSL was positively associated with body fat percentage ( P =0·008) and fat mass index ( P =0·026). When stratifying the group according to physical activity recommendations, the aforementioned associations were only maintained for non-compliers. Cluster analysis showed that the low-ED and high-MVPA group presented the healthiest profile for all adiposity and CRF. These findings could partly explain inconsistencies in literature, as we found that different ED calculations entail distinct results. Physical activity levels and excluding under-reporters greatly influence the associations between ED and adiposity in children with overweight and obesity.